2014
DOI: 10.1038/nrneph.2014.31
|View full text |Cite
|
Sign up to set email alerts
|

Novel targets of antifibrotic and anti-inflammatory treatment in CKD

Abstract: Chronic kidney disease (CKD) is becoming a worldwide epidemic, driven largely by the dramatic rise in the prevalence of diabetes and obesity. Novel targets and treatments for CKD are, therefore, desperately needed—to both mitigate the burden of this disease in the general population and reduce the necessity for renal replacement therapy in individual patients. This Review highlights new insights into the mechanisms that contribute to CKD, and approaches that might facilitate the development of disease-arrestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
116
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(116 citation statements)
references
References 114 publications
0
116
0
Order By: Relevance
“…Moshe Levy et al [57] showed, in agreement with other studies, in both insulin deficient and insulin intact db/db animals, that SGLT2 inhibition results in a decrease in proteinuria and inflammation in the kidney. In addition, they showed that these beneficial effects are associated with significant decreases in mesangial expansion, accumulation of extracellular matrix proteins, fibrillary collagens, and prevention of podocyte loss, which are the hallmarks of diabetic nephropathy [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moshe Levy et al [57] showed, in agreement with other studies, in both insulin deficient and insulin intact db/db animals, that SGLT2 inhibition results in a decrease in proteinuria and inflammation in the kidney. In addition, they showed that these beneficial effects are associated with significant decreases in mesangial expansion, accumulation of extracellular matrix proteins, fibrillary collagens, and prevention of podocyte loss, which are the hallmarks of diabetic nephropathy [62].…”
Section: Discussionmentioning
confidence: 99%
“…Since SGLT2 inhibitors act via a different mechanism than other oral anti-hyperglycemic drugs, they can be first line treatment in T2DM and DN in the future [62,65].…”
Section: Discussionmentioning
confidence: 99%
“…A number of agents which more or less specifically inhibit TGF-are in clinical trials, including fresolimumab (a TGFantibody), pirfenidone, tranilast and tranilast analogues (20,21). Little data are available so far and none of the clinical trials has been performed in the transplant allograft situation.…”
Section: Key Molecular Effector Systems and Therapies In Renal Fibrosismentioning
confidence: 99%
“…TGF-bs are widely expressed and act on almost every cell type by engaging signaling molecules of the Smad and non-Smad families such as small GTPase Ras/Rho molecules. A large number of therapeutic options to interfere with TGF-bioactivity has been tested in preclinical studies including antagonistic antibodies, soluble receptor forms, agents that inhibit downstream intracellular signaling molecules (in particular Smads), RNA interference and targeting of TGF--induced micro-RNAs (20,255,(257)(258)(259)(260). Other antifibrotic interventions in the system are focused on modulators of TGF-bioactivity, such as BMP-7 or BMP antagonists such as USAG-1 (253,261,262).…”
Section: Key Molecular Effector Systems and Therapies In Renal Fibrosismentioning
confidence: 99%
See 1 more Smart Citation